EFFECT OF PETROLUME REFINERY WASTEWATER ON PLANT GROWTH IN INTEGRATED MICROBIAL FUEL CELL-CONSTRUCTED WETLANDS SYSTEMS - & Ismail, Hussain (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Three identically designed microbial fuel cell-constructed wetland (MFC-CW) systems were constructed and setup in this study for simultaneous biotreatment of petroleum refinery wastewater (PRW) and bioelectricity generation. MFC-CW1 and MFC-CW2 were planted with Canna indica, and Phragmites australis, respectively. MFC-CW3 was unplanted and considered as the control. These three systems were operated simultaneously in a batch mode for two cycles to evaluate the effect of PRW biotreatment on the growth and development of the selected plants and the potential of generated bioelectricity as well. The operation period for each cycle was 8 days. Results demonstrated that maximum removal efficiency of the organic content represented as chemical oxygen demand (COD) were 98.75%, 97.67%, and 97.83% observed in MFC-CW1, MFC-CW2, and MFC-CW3, respectively, whereby, the highest power generation were 19.86, 19.04, and 18.7 mW/m2, respectively. On the other hand, both types of plants exhibited notable growth and new sprouts appearance. The potential convergence of the results in the three MFC-CWs, and the healthy growth of both types of plants clearly and potentially indicated that the dominant mechanism of organic pollutant removal was via biodegradation process by the anodic biofilm in the MFC rather than being removed by phytoremediation process.